Beyond Empathy: Vulnerability, Relationality and Dementia. Issue 2 (15th March 2019) - Petherbridge, Danielle
ABSTRACT: This paper brings together a phenomenological and vulnerability-theoretic approach to dementia. The paper challenges the view that subjects with dementia can simply be understood in terms of diminished cognitive capacities or that they have lost all vestiges of personhood or the capacity for meaningful interaction. Instead, drawing on vulnerability theory and the phenomenological work of Kristin Zeiler and Lisa Käll, an alternative view of persons with dementia is offered that is based on intersubjective and intercorporeal relations and accomplishments. A vulnerability approach to dementia is developed that not only provides the basis for empathetic responses to illnesses such as dementia but also points to the intersubjective constitution of subjects more generally. The argument developed is that the notion of vulnerability designates a form of openness to others and that such openness is a precondition for empathy.